Pengaruh Peraturan Daerah Tentang Larangan Penggunaan Kantong Plastik pada Perusahaan Retail di Kota Banjarmasin - Dyah Sri Wulandari; Maya Rezeki Angriani; Dewi Aina (Universitas Batanghari, 2022)
This study focus to analyze how much influence local regulations have on the prohibition of the use plastic bags in retail companies in the Banjarmasin city. The method used is quantitative method with explanatory research type. The sample in this study used the purposive sampling technique. The sample amounted in this study is 100 modern/retail shops in the city of Banjarmasin. Then the data is processed using the SmartPLS computer program. Mayor Regulation (Perwali) Banjarmasin Number 18 of 2016 regarding or regarding Reduction in Using Plastic Bags, both from the consumer side and from the modern retail store. The results of this study indicate that the Banjarmasin City Regulation (X) has a significant effect on the Use Plastic Bags (Y), especially in modern/retail stores, it has been implemented well and can be accepted by consumers.